Zapisz wyrażenia, nie używając nawiasów. Zredukuj wyrazy podobne .
a) 2a + (3a - 7)
b) x - (2x - 3)
c) 3x - (y - 2x)
d) -(3a + 6) - 4
e) -(2x - 1) - (3x + 1)
f) (4a - 7b) - (2a + 3b)
g) (2p - r) + (2r - p)
h) (x + y) + (x - z ) + (z - y)

2

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-26T13:15:09+01:00
A) 2a + (3a - 7)
2a + 3a - 7
5a-7

b) x - (2x - 3)
x - 2x + 3
-x+3

c) 3x - (y - 2x)
3x - y + 2x
5x-y

d) -(3a + 6) - 4
-3a - 6 - 4
-3a-10

e) -(2x - 1) - (3x + 1)
-2x + 1 - 3x - 1
-5x

f) (4a - 7b) - (2a + 3b)
4a - 7b - 2a - 3b
2a-10b

g) (2p - r) + (2r - p)
2p - r + 2r - p
p+r

h) (x + y) + (x - z ) + (z - y)
x + y + x - z + z - y
2x

5 4 5
2010-01-26T13:18:27+01:00
A) 2a + (3a - 7)=2a+3a-7=5a-7
b) x - (2x - 3)=x-2x+3=-x+3
c) 3x - (y - 2x)=3x-y+2x=5x-y
d) -(3a + 6) - 4=-3a-6-4=-3a-10
e) -(2x - 1) - (3x + 1)=-2x+1-3x-1=-5x
f) (4a - 7b) - (2a + 3b)=4a-7b-2a-3b=2a-10b
g) (2p - r) + (2r - p)=2p-r+2r-p=p+r
h) (x + y) + (x - z ) + (z - y)=x+y+x-z+z-y=2x
3 5 3